Stanko Petrič, prvi slovenski prevajalec in komentator Savitri - Pacheiner-Klander, Vlasta (Primerjalna književnost, 2012)
This article discusses the first Slovenian translation of Savitri and Satyavan, an episodic story from the Mahabharata. It was published in 1923 by Stanko Petrič, a comparative linguistics student. The barely known translator's life is reconstructed based on archival documents. The analysis of the translation is based on a comparison with the original published in the Sanskrit textbook by Hermann Camillo Kellner.
Keywords: Petrič, Stanko, 1903-1924; staroindijska književnost; epika; Mahabharata; Savitri; Sanskrit; sanskrt; prevodi v slovenščino